Superficial Automated Keratopigmentation for Iris and Pupil Simulation Using Micronized Mineral Pigments and a New Puncturing Device: Experimental Study. Issue 9 (September 2017) - Rodriguez, Alejandra E.; Amesty, Maria A.; El Bahrawy, Mohammed; Rey, Severino; Alio del Barrio, Jorge; Alio, Jorge L.
Abstract : Purpose: To study the outcomes and tolerance of micronized mineral pigments for corneal tattooing, using a superficial automated keratopigmentation (SAK) technique in an experimental animal model and a new puncture device to inject the pigments into the corneal stroma. Methods: Forty eyes of 40 New Zealand rabbits were included in this study. The animals were divided into groups A and B. Both groups underwent SAK using a new automated keratopigmentation device. Micronized mineral pigments were injected through the epithelium into the corneal stroma to replicate the iris color in 25 eyes (group A), and black color was used to replicate the pupil in 15 eyes (group B). Slit-lamp examination was performed to evaluate the outcome. Histopathological examination was also performed to ascertain the presence of pigment dispersion, inflammation, and/or neovascularization. Results: All 40 eyes showed good cosmetic appearance after keratopigmentation. No intraoperative complications were detected. At the first week, mild or moderated conjunctival injection was observed in 13 eyes and transitory corneal epithelial defects were also detected in 27 eyes. Examination was unremarkable 2, 4, and 6 months after surgery. No neovascularization was detected in any case in the histopathology study. Conclusions: SAK using a new automated puncture device and micronized mineral pigments achieved good cosmetic outcomes for iris and pupil simulation. This method could be a valid alternative to treat serious cosmetic eye problems that affect the superficial cornea or functional problems, such as photophobia or diplopia secondary to iris defects or trauma. Abstract : Supplemental Digital Content is Available in the Text.